Fructose-Induced Carbonyl/Oxidative Stress in S. cerevisiae: Involvement of TOR - Bohdana V. Valishkevych; Ruslana A. Vasylkovska; Liudmyla M. Lozinska; Halyna M. Semchyshyn (Biochemistry Research International)
The TOR (target of rapamycin) signaling pathway first described in the budding yeast Saccharomyces cerevisiae is highly conserved in eukaryotes effector of cell growth, longevity, and stress response. TOR activation by nitrogen sources, in particular amino acids, is well studied; however its interplay with carbohydrates and carbonyl stress is poorly investigated. Fructose is a more potent glycoxidation agent capable of producing greater amounts of reactive carbonyl (RCS) and oxygen species (ROS) than glucose. The increased RCS/ROS production, as a result of glycoxidation in vivo, is supposed to be involved in carbonyl/oxidative stress, metabolic disorders, and lifespan shortening of eukaryotes. In this work we aim to expand our understanding of how TOR is involved in carbonyl/oxidative stress caused by reducing monosaccharides. It was found that in fructose-grown compared with glucose-grown cells the level of carbonyl/oxidative stress markers was higher. The defects in the TOR pathway inhibited metabolic rate and suppressed generation of glycoxidation products in fructose-grown yeast.